Corporate governance effect on firms' performance - evidence from the UAE - Farhan, Ayda; Sheikh Obid, Siti Normala; Annuar, Hairul Azlan (Emerald Group Publishing Ltd., 2017)
Purpose – The purpose of this paper is to show the effect of the corporate governance (CG) on firms’ performance in the United Arab Emirates (UAE). The governance mechanisms employed in this study are board size, board independence and audit committee’s (AC) characteristics. The examined AC characteristics are: AC member’s independence, number of financial experts in the committee, ratio of meetings held during the year, and the incentives received by the AC members. Design/methodology/approach – This paper uses all the public listed corporations in the UAE financial markets. The secondary data for four years are used starting from 2010 where the mandatory corporate governance code had been mandated. Findings – Board independence has been found to negatively affect firms’ performance. AC meetings and financial experts’ ratio did not affect firm’s performance, while AC incentives and AC independence negatively affected firms’ performance. Originality/value – This study is supposed to fill the gap of the lack in CG studies based on fast growing economy which is UAE. Besides, this research investigates the AC’s characters’ effect on firms’ performance which was rarely covered in literature. Keywords Corporate governance, Business performance, Auditing